A Global Perspective on Cardiovascular Risk Factors by Educational Level in CHD Patients: SURF CHD II - Anna Marzà-Florensa; Ilonca Vaartjes; Ian Graham; Kerstin Klipstein-Grobusch; Diederick. E Grobbee; SURF CHD II collaborators (Ubiquity Press, 2024)
Background: Clinical guidelines recommend lifestyle modifications and medication use to control cardiovascular risk factors in coronary heart disease (CHD) patients. However, risk factor control remains challenging especially in patients with lower educational level. Objective: To assess inequalities by educational level in the secondary prevention of CHD in the Survey of Risk Factors in Coronary Heart Disease (SURF CHD II). Methods: SURF CHD II is a cross-sectional clinical audit on secondary prevention of CHD, conducted during routine clinical visits in 29 countries. The easy-to-perform design of the survey facilitates its implementation in settings with limited resources. We reported risk factor recording, attainment of guideline-defined risk factor targets, and treatment in CHD patients. Differences by educational level in target attainment and treatment were assessed with logistic regression stratified for high- (HIC), upper middle- (UMIC), and lower middle-income (LMIC) countries. Results: SURF CHD II included 13,884 patients from 2019 to 2022, of which 25.0% were female and 18.6% had achieved only primary school level. Risk factor recording ranged from 22.2% for waist circumference to 95.6% for smoking status, and target attainment from 15.9% for waist circumference to 78.7% for smoking. Most patients used cardioprotective medications and 50.5% attended cardiac rehabilitation. Patients with secondary or tertiary education were more likely to meet targets for smoking, LDL cholesterol and physical activity in HICs and LMICs; for physical activity and triglycerides in UMICs; but less likely to meet targets for blood pressure in HICs and LDL <1.4mmol/L in UMICs. Higher education was positively associated with medication use and cardiac rehabilitation participation. Conclusion: CHD patients generally have poor attainment of risk factor targets, but patients with a higher educational level are generally more likely to participate in cardiac rehabilitation, use medication, and meet targets. Main messages • Target attainment and participation in cardiac rehabilitation are poor in CHD patients globally. • Patients with higher education are more likely to meet risk factor targets, showing health inequities in secondary prevention of CHD. • The association between education and risk factor target attainment and treatment varies with country income level.